Level Berpikir Geometri Peserta Didik Berdasarkan Teori Van Hiele pada Materi Bangun Ruang Sisi Datar - Anna Cesaria; Tatang Herman; Jarnawi Afgani Dahlan (Universitas Hamzanwadi, 2021)
According to Van Hiele, in understanding geometry, students need to understand five stages, namely stage 1 (introduction stage), stage 2 (analysis stage), stage 3 (sequencing stage), stage 4 (deduction stage), and stage 5 (accuracy stage). Each student has different geometric thinking abilities. This study aims to examine the geometric abilities of junior high school students in the material of flat-sided geometry according to Van Hiele's Theory. This research belongs to the type of qualitative research with a case study design. It was conducted at three schools in Padang, West Sumatra, Indonesia. The subjects were students of SMP Negeri 1 Padang, SMP Negeri 7 Padang, and SMP Negeri 25 Padang. Data collection was carried out using tests, interviews, and documentation. Data analysis was carried out with the stages of data reduction, data presentation, and data verification or drawing conclusions. The data originality technique was carried out with the triangulation technique, where the researcher compared the test data with the results of interviews with students. Of the 94 students (male = 38, female 56) tested based on the geometric thinking level of Van Hiele Theory, 92.55% of the students reached the Van Hiele thinking stage at the visualization level. As many as 45.74% of students reached the level of geometric analysis, and 6.38% of students reached the level of abstraction. For the level of deduction and accuracy, no one has been able to solve the problem. The results obtained in this study are that most students are still at stages 1 and 2, unlike van Hiele's opinion, which revealed that the level of geometric thinking for junior high school students is at level 3. According to the study results, it is essential to carry out further checks on the level of geometric thinking of junior high school students in other areas.